BMC Health Services Research - Song, Haihan; Nimbalkar, Vaishnavi; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Health Services Research is an open access peer reviewed journal that considers articles on all aspects of health services research. The journal has a special focus on digital health, governance, health policy, health system quality and safety, healthcare delivery and access to healthcare, healthcare financing and economics, implementing reform and the health workforce. BMC Health Services Research welcomes articles in the following broad areas of research: Designing and implementing health system reform eHealth, mHealth and informatics Health policy, politics and power Health system quality and safety Healthcare delivery and access to healthcare Healthcare financing and economics Healthcare governance and management The health workforce As a BMC Series journal, BMC Health Services Research does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field.
Keywords: Medical care; Health services administration; Medical economics; Medical policy; Biomedical engineering; Health Care; Health Care Management; Health Economics; Health Policy; Medical and Health Technologies